Infância, sexualidade e educação através dos desenhos animados - Pereira, Larissa Citrângulo [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
This article discusses the import o clock work and child sexuality for the overall development of children. To them as individuals socially and historically constitutional. Of that uses this instrument to express vivences and sensation. Es often unnoticed by adults look. We seek to ensnare a set of reflex. It’s fundamental about the multiples management possibilities you Rich and practical knowledge of the obvious sexuality analyzing brands present in the cartoons that are part of everyday life and education. The child to speak about the body of knowledge that the child to have, and what their relations with the same body, weaving some notes on sexuality and space the discovery, demonstrating the sensitivity surrounding the object of our study. During the course of this research, we remain based on studies of the reference you? Rich presented by: Freud (1997), Camargo and Ribeiro (1999), La Taille (2002) and Souza (1997). Where the main purpose for analyze the educational development of children having as a basis for an Dialysis cartoon that can serve as subside s difficulties in practice teacher, immersing ourselves in the gap left by the way deficit of educators regarding spec. I now proposed to issue, contributing, at least in part, to the improvement of Education and the professionals who work in it.

Objetivamos discutir a importância do trabalho com a sexualidade infantil para o desenvolvimento global da criança, enquanto sujeito social e historicamente constituído, que usa deste instrumento para expressar vivências e sensações muitas vezes despercebidas pelo olhar adulto. Procuramos enredar um conjunto de reflexões fundamentais sobre as múltiplas possibilidades de manejo teórico e prático das manifestações da sexualidade analisando marcas presentes nos desenhos animados que fazem parte do cotidiano e da educação infantil, ao dissertarmos sobre o conhecimento de corpo que a criança possui e quais suas relações com esse mesmo corpo, tecendo alguns apontamentos sobre a sexualidade como espaço de descobertas, demonstrando a delicadeza que envolve nosso objeto de estudo. No decorrer do percurso deste trabalho de pesquisa, mantemo-nos baseados em estudos do referencial teórico apresentado por: Freud (1997), Camargo e Ribeiro (1999), La Taille (2002) e Souza (1997). Onde o principal propósito é analisar os aspectos educacionais do desenvolvimento da criança tendo como base a análise dos desenhos animados e sua relação com as discussões sobre o tema, inserindo-nos na lacuna deixada pela formação deficitária de educadores no tocante específico ao tema doravante proposto, contribuindo, ao menos em parte, para a melhoria da Educação e dos profissionais que nela atuam.
Keywords: Orientação educacional; Crianças - Desenvolvimento; Crianças - Comportamento sexual; Educação e gênero; Corpo; Sexuality; Development; Cartoons